CANCEL CULTURE AND ACADEMIC FREEDOM: A Perspective from Democratic-Deliberative Education Philosophy - Trio Kurniawan; Rambang Ngawan; Yudas Alno; Agus Herianto (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2022)
Cancel culture (or also known as call-out culture) is a social and cultural phenomenon that has been gaining global attention in the recent years. Public figures, company brands or institutions can be ostracized or boycotted only on the basis of disagreeing with the statement or visions of the sympathizers or the ideologues of this so-called cancel culture. This phenomenon has also slowly infiltrated the world of education and some researchers would even argue that cancel culture has its seminal growth beginning from the academe itself. Thus, with that regard, this article will critically analyze the phenomenon of cancel culture particularly in the realm of education. Anchored in the principle of academic freedom, this article shall put into scrutiny the presence of cancel culture and its presuppositions and ramifications in education. And in order to achieve such telos, as a qualitative study, this article has employed an analytical-critical reflection as its method. In this academic endeavor, then, the researchers shall rely on the perspective of Deliberative-Democratic Education Philosophy as its benchmark.